"Éistear le mo ghlór!": Máirtín Ó Cadhain's Cré na Cille and postcolonial modernisms. Issue 3 (3rd July 2018) - Byrne, Eoin
ABSTRACT: Since 2015, there have been two English language translations of Máirtín Ó Cadhain's most acclaimed novel, Cré na Cille . Now that his work is available to a larger readership than ever before, it is an opportune moment to revaluate Ó Cadhain's position within Irish literary space, and to investigate how his work is received in contexts outside of Ireland. His most celebrated novel is deeply rooted in the Irish language literary tradition, while also containing transnational modernist elements; indeed, it extends the remit of what constitutes modernist literary production, while concurrently problematising traditional definitions of modernist writing. Considering the postcolonial and minority language contexts in which Ó Cadhain was operating, a more nuanced critical terminology is needed to negotiate between the specific cultural and linguistic origins of his work and its interaction with the broader transnational modernist canon. A concept like "postcolonial modernism" can enhance understandings of modernist literary production in general, and literary production during Ireland's postcolonial moment in particular.